2010
DOI: 10.1002/pip.991
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time reliability test for a CPV module based on a power degradation model

Abstract: Models based on degradation are powerful and useful tools to evaluate the reliability of those devices in which failure happens because of degradation in the performance parameters. This paper presents a procedure for assessing the reliability of concentrator photovoltaic (CPV) modules operating outdoors in real-time conditions. With this model, the main reliability functions are predicted. This model has been applied to a real case with a module composed of GaAs singlejunction solar cells and total internal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
0
14
0
5
Order By: Relevance
“…Additionally, our predictions on the basis of temperature stress have a limited validity. For example, we are not absolutely sure if the failure mechanism that appears in our tests will be the same as that in real operation, although previous experiments for 1‐year real operation with this type of cells shows that they suffer a very low degradation without any catastrophic failures. This is consistent with our experiments, but it is necessary to confirm that the degradation mechanism for long time operation in field is the same in order to apply the numerical reliability and warranty results obtained in these tests.…”
Section: Validity Range Of Predictionsmentioning
confidence: 81%
“…Additionally, our predictions on the basis of temperature stress have a limited validity. For example, we are not absolutely sure if the failure mechanism that appears in our tests will be the same as that in real operation, although previous experiments for 1‐year real operation with this type of cells shows that they suffer a very low degradation without any catastrophic failures. This is consistent with our experiments, but it is necessary to confirm that the degradation mechanism for long time operation in field is the same in order to apply the numerical reliability and warranty results obtained in these tests.…”
Section: Validity Range Of Predictionsmentioning
confidence: 81%
“…The most critical functions, the connectivity and data transmission functions, passed the test. It was demonstrated that the datalogger is highly reliable [28,29], measuring correctly even at 55 • C.…”
Section: Discussionmentioning
confidence: 99%
“…The main objectives of the reliability analysis are to evaluate the time accelerated aging factor between tests at any solar cell junction temperatures, 17,18 and to calculate the reliability and mean time to failure at normal working conditions. For thermal accelerated tests, Arrhenius' law is used to extrapolate the power time evolution for any junction temperature.…”
Section: Discussionmentioning
confidence: 99%